Public health interventions: evaluating the economic evaluations - Martin Forster; Paolo Pertile (SAGE Publishing, 2013)
Recent years have witnessed much progress in the incorporation of economic considerations into the evaluation of public health interventions. In England, the Centre for Public Health Excellence within the National Institute for Health and Care Excellence works to develop guidance for preventing illness and assessing which public health interventions are most effective and provide best value for money...